중소병원 간호사의 역할갈등이 긍정심리자본과 조직효과성에 미치는 영향 - 황경미(Kyeong-Mi Hwang) (한국콘텐츠학회 논문지, 19(1), 2019)
This study is a descriptive research study to identify the role conflicts, positive psychological capital, organizational effectiveness, and factors affecting organizational effectiveness of nurses in small hospitals. The subjects of the study were nurses working in three small and medium-sized hospitals located in A city and 255 copies were used for final data analysis. The results showed that the roles of role conflict, isolation, role ambiguity, and resource shortage had a significant negative effect on organizational effectiveness. Role ambiguity and resource shortage of role conflict were significant (-) on positive psychological capital. Positive optimism, positive self efficacy, hope and optimism have a positive (+) effect on organizational effectiveness. Based on the results of this study, it is necessary to develop a variety of programs to reduce role conflict and demonstrate positive psychological capital in order to improve the organizational effectiveness of nurses in small and medium-sized hospitals. 본 연구는 중소병원 간호사의 역할갈등, 긍정심리자본, 조직 효과성의 관련성을 파악하고, 조직효과성에 영향을 미치는 요인을 규명하기 위한 서술적 조사연구이다. 연구대상은 A시에 소재하고 하는 3개의 중소병원에 근무하는 간호사를 대상으로 하였으며 255부를 최종 자료분석에 사용하였다. 연구결과 역할 갈등의 역할 고립과 역할 모호, 자원 부족은 조직효과성에 유의한 부(-)의 영향을 미치는 것으로 나타났고, 역할 갈등의 역할 모호와 자원 부족은 긍정심리자본에 유의한 부(-)의 영향을 미치는 것으로 나타났으며, 긍정심리자본의 자기효능감과 희망, 낙관주의는 조직효과성에 유의한 정(+)의 영향을 미치는 것으로 나타났다. 본 연구 결과를 토대로 중소병원 간호사의 조직효과성을 증진시키기 위해서는 역할갈등을 감소시키고 긍정심리자본을 발휘할 수 있도록 다양한 프로그램 개발이 필요할 것으로 생각된다.